The Indolylcoumarin COUFIN Exhibits Potent Activity Against Renal Carcinoma Cells without Affecting Hematopoietic System - Champelovier, Pierre; Barbier, Pascale; Daras, Etienne; Douillard, Soazig; Toussaint, Bertrand; Persoon, Virginie; Curri, Veronique; Peyrot, Vincent; Combes, Sebastien (Anti-Cancer Agents in Medicinal Chemistry, 2014)
The present work describes the anticancer activity of a new indolylcoumarin named COUFIN and more specifically, its efficiency against clear cell renal carcinoma (CCRC). COUFIN inhibited microtubule formation and bound on tubulin to or near the colchicine site. In vitro, COUFIN showed potent anticancer activity on renal carcinoma cells (RCC) both in monolayer (2D culture) (IC50 of 88±8 nM) and multicellular tumor spheroid (3D culture) (IC50 of 180±20 nM). The compound blocked cell cycle transition at G2/M phase, induced a subsequent apoptotic process but did not modulate clonal growth of CFU-GM. On the other hand, the coumarin derivative decreased the activity of P-gp and BCRP but was not substrate for these ABC pumps. In vivo, the indolylcoumarin increased the survival rate after 3 weeks of treatment. Based on the present study, COUFIN was identified as a bifunctional molecule able to inhibit renal carcinoma cells proliferation without being effluxed by ABC proteins. Thus COUFIN could be a promising chemotherapeutic agent for treating tumor cells over-expressing efflux pumps and tumor cells irrigated by vessels lined with endothelial cells responsible of poor distribution of conventional anticancer agents.
Keywords: tubulin